New tunable all-fiber optical comb filter based on machzehnder interferometer - Islam, Md. Shafiqul (2011)
This dissertation presents theoretical model and experimental construction and development of two tunable all-fiber comb filters based on Mach-Zehnder interferometer (MZI). The unique demonstration of this dissertation is the spectral spacing tunability and peak wavelength position shifting within the free spectral range (FSR) of the output transmission spectrum. There are two designs of MZI-based comb filter studied in the dissertation. Firstly, a tunable all-fiber comb filter based on dual-pass MZI is demonstrated in which one segment of polarization maintaining fiber (PMF) and one polarization controller (PC) are inserted in the second loop of conventional MZI. The PMF segment consists of lengths L1=6 m and L2=3 m are spliced at 900 about their principle axes to each other. Half wave plate (HWP) of PC is used for changing the effective length of the PMF segment from its maximum |L1+L2| to minimum |L1-L2|. The separation between two peaks, namely as spectral spacing can be adjusted to any desired value in between 0.72 nm to 2.00 nm using the HWP. Shifting of peak wavelength position within the FSR is demonstrated using a quarter wave plate (QWP) of PC. Extinction ratios are observed in between 16 dB to 18 dB through out the experiment. The proposed dual-pass MZI-based comb filter still uses two fiber couplers which makes the design vulnerable to environmental perturbations. In order to rectify this problem, single-core fiber MZI-based tunable comb filter is demonstrated. One PMF segment consists of lengths L1=7.80 m and L2=4.60 m are spliced between two single mode fibers (SMFs) at 450 and 00 respectively. One PC is inserted in this alignment. The Spectral spacing can be adjusted to any desired value in between 0.55 nm to 1.95 nm using HWP. The peak wavelength position can also be shifted over the entire FSR with extinction ratios in between 18 dB to 20 dB. For both comb filters, the tunability of spectral spacing and peak wavelength can be achieved by tuning the HWP and QWP of PC respectively. In addition to this, the spectral spacing can also be tuned by changing the surrounding temperature without adjusting the HWP. On the other hand, the peak wavelength shift can also be obtained by applying stress on the PMF segment without rotating the QWP. Therefore, these comb filters can be utilized as a temperature or strain sensor. Besides these potential applications, these comb filters have been tested in fiber lasers to generate multiple lasing channels simultaneously. At room temperature, more than 30 channels within 3 dB peak power variation are recorded from an Erbium-doped fiber laser incorporating the proposed comb filters.